Evaluar las propiedades del purín de humus de lombriz (Eisenia Foetida) obtenido a partir de diferentes raquis. - Muñoz Sánchez, Galo Israel (2015)
This research entitled "Assessing the properties of manure vermicompost (Eisenia foetida) obtained from different spine" will be the place in the Experimental Farm "Dam" property of the State Technical University of Quevedo (UTEQ), the which it is located at km 6-San Carlos Quevedo, province of Los Rios route. Its geographical location is 01 ° 06 'south latitude and 79 ° 29' West longitude, located at a height of 120 meters above sea level. The general objective was wanted to achieve: Analyze quality vermicompost manure obtained from different spine area Quevedo. To achieve this objective plated Specific objectives: 1) to evaluate the chemical properties of the worm manure treatments, 2) determine the concentrations of humic and fulvic acids present in the manure worm, 3) establish the presence of microorganisms in treatments in studios, 4) analyze the production costs of manure worm. The results indicate that all treatments proposed for this study such as palm rachis; rachis of banana and coconut rachis more cattle manure at rates of 75% - 25%; 50% - 50% and 25% - 75% respectively determined that the highest temperature reached in the preparation of humus was 24 ° C and not less than 19 ° C, as the moisture that is handled within the values optimal (70-80%) and had a pH of 8.1 degree of acidity, related to optimal values suggested by researchers for transforming into humus plant waste by earthworms. The highest concentration of macronutrients was obtained with the composition of African palm rachis 25% and livestock manure 75% while at the level of microelements treatment response was higher in the combination of palm rachis 75% and manure Cattle 25%. The slurry also contains a good ratio of C/N with an average of 23.2 statistically superior to the other treatments with averages between 8.9 and 21.46. Humic and fulvic acids presenting (w/w) between 0, 87 to 0.56 and from 0.45 to 0.37 respectively. The increased presence of microorganisms was obtained in treatments involving African palm spine in combination with cattle manure. The increased presence of microorganisms were Trichoderma, Penicillium, Cladosporium, Aspergillus sp and bacterial load 1,91X105 5.65X104 to bringing quality worm manure is really profitable use by the characteristics and quality of its checks components and through this research are made known, recommending conduct research in various cultures to determine the effectiveness of manure in its development.